VariClose® vein sealing system is inferior to endovenous laser ablation for the treatment of varicose veins - Balaz, Peter; Rokosny, Slavomir; Whitley, Adam (Vascular, 2022)
BACKGROUND: One of the three commercially available cyanoacrylate venous glues used for the treatment of saphenous vein insufficiency is the VariClose® vein sealing system. Previous studies have documented a high rate of occlusion and minimal postoperative complications. The aim of this study was to compare occlusion rates and clinical outcomes of endovenous laser treatment with the VariClose® vein sealing system in the treatment of truncal vein insufficiency. PATIENTS AND METHODS: Retrospective non-randomized single center study with prospectively collected data comparing endovenous laser treatment and VariClose® procedures between April 2018 and November 2019. RESULTS: VariClose® was used in 27 patients (30 veins) and endovenous laser treatment in 42 patients (51 veins). The occlusion rate at one, three, and six months were 96%, 85%, and 65% for VariClose® procedures and 100%, 100%, and 97% for endovenous laser treatment procedures (p = 0.01), respectively. Reduction of VCSS scores before treatment and at the last postoperative follow-up visit in the VariClose® group dropped by an average of 1.8 ± 1.6 and in the endovenous laser treatment by an average of 3.3 ± 2.9 (p = 0.01). CONCLUSION: VariClose® vein sealing system is inferior to endovenous laser treatment as a treatment option for varicose veins as it has a higher recanalization rate.
Keywords: varixy; Venous Insufficiency; žilní insuficience; Retrospective Studies; vena saphena; retrospektivní studie; Varicose Veins; Treatment Outcome; lidé; Saphenous Vein; Laser Therapy; Humans; laserová terapie; výsledek terapie